Cultivar x Environment Interaction and Stability in Low-Cost Maize (Zea mays L.) cultivars (Research, Society and Development, 2023)
Gene expression studies through genotype x environment interaction and stability are used by plant breeding programs to identify cultivars that present predictable and optimal behavior for subsequent cultivar recommendation. The objective of this present study was to identify maize cultivars with stable growth and productivity and low acquisition cost through the evaluation of the cultivar x environment interaction and production stability in the municipality of Vilankulo, Mozambique. Four maize cultivars were evaluated in six environments composed of the combination of two planting seasons and three levels of nitrogen fertilization. The experiments were conducted in the 2019/20 and 2020 agricultural seasons at the experimental area of UEM-ESUDER. In each experiment, a randomized complete block design (RCBD) was used in a 4 x 3 factorial arrangement with three replications, comprising four cultivars and three levels of nitrogen fertilization. It was concluded that the order of responses in the growth and productivity of cultivars changes with the shift in planting season and applied nitrogen fertilization level. The VPAL cultivar is the most productive and stable for the municipality of Vilankulo, Mozambique.